OPTIMIZING PERFORMANCE: THE ROLE OF STRATEGIC HUMAN RESOURCE MANAGEMENT IN ENHANCING OPERATIONAL OUTCOMES WITHIN NGOS - Paresh, Shantanu; Sangeeta, Birjepatil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The impact of Strategic Human Resource Management (SHRM) practices on the operational results of Non-Governmental Organizations (NGOs) is investigated in this research paper. Optimizing performance via strategic HR management practices is essential since NGOs have particular problems in resource allocation and human capital management. Using a sample of 150 respondents from diverse NGOs, the study uses quantitative data analysis to evaluate the impact of SHRM on organizational commitment, employee happiness, and operational efficiency. The results show that implementing SHRM practices significantly improves operational outcomes, indicating that NGOs may increase their efficacy and sustainability by implementing strategic HR initiatives.